A representação social de uma cultura funk e das favelas - Siqueira, Flávia Conceição da Rocha (2015)
The world of funk is represented in and through society from a biased point of view. Along Brazilian history, this group has demonstrated not only aspects of a culture of resistance in the national scenario, but also the ability to convey the minority voice of a social margin. Departing from the understanding that it is in discourse that the members of this group express the mental constructions they build of the funk culture and their life experiences in the favelas, this research critically analyzes how this social representation is construed in some lyrics. We draw upon sociocognitive approach (VAN DIJK 2012a, 2012b, 2012c, 1999), which works the notion of context as a kind of mental model. We analyze which contextual structures (setting, participants, actions, personal and individual cognition) and textual structures (local semantics: evidentials, metaphors, lexical items; global semantics: positive self-representation, negative other-presentation; rhetorical structures: euphemism, irony, antithesis, syntax) become evident in the lyrics thus representing culture, beliefs, ideologies and life experiences of this particular group through specific context models. Moreover, we draw upon the basic notion of the social representation theory of discursive actors (VAN LEEUWEN, 1997). We also resort on Hershmann (2005) and Vianna (1987; 1990) and their research on funk. Among several cultural aspects composing the base for the analysis of a certain group, this work is justified in the sense that the lyrics of the musical genre – in its many nuances – is one of the means of representing (or presenting) the favelas and the funk supporters. We are engaged with GEDIM (Grupo de Estudos sobre o Discurso Midiático - Media Discourse Study Group), which studies issues of the media related to social minorities. Since the media generally builds representations of many social groups non-corresponding to the intragroup reality, taking part in the research group has allowed me to see the discursive control possessed by the symbolic elites. This furthermore justifies this research for, against the stereotype view that society has from funk and the favelas, we want to verify how the lyrics work this representation. Having presented our topic, we have selected funk songs from the www.letras.mus website for an analytical/interpretative-qualitative research. We have selected 10 songs about funk and the favelas among 5.776 hits, corresponding to approximately 274 artists. In our results, we found discursive elements, which highlight the representation of the funk and the favela culture, emerging from critics-outcries the songs represent as of existing relations between the social, political and economic system of the country.